Pemberdayaan Guru SD Kabupaten Bengkalis melalui Integrasi Kegiatan Coding Berbasis STEM untuk Meningkatkan Kemampuan Computational Thinking - Rifqa Gusmida Syahrun Barokah; Neni Hermita; M. Jaya Adi Putra; Suroyo Suroyo; Nur Asiah; Gustimal Witri; Dewi Nasien (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
Characterized by rapid technological progress, education today demands teachers who are not only digitally literate but also capable of fostering computational thinking (CT) in students. However, many elementary teachers still face challenges in integrating coding and STEM principles into classroom learning. This community service program was designed to empower elementary school teachers in Bengkalis Regency through the integration of STEM-based coding to enhance their CT skills. The two-day program involved 50 teachers from 22 schools and employed a combination of conceptual sessions on deep learning and CT, unplugged coding practices using Kids First Coding and Robotics (Smart Bricks), plug-in coding practices with Scratch for Arduino (S4A) and workshops to develop STEM-based science lesson plans (RPP) showcased through microteaching. Results revealed an average post-test CT score of 79.3, with 82% of teachers achieving mastery (≥70). Teachers successfully created innovative lesson plans integrating CT into science topics such as phase changes of matter and the solar system. The microteaching sessions showed that participants could contextualize coding-STEM learning effectively. Teacher reflections emphasized the need for continuous training, sufficient facilities, and the establishment of a coding-STEM teacher community. In conclusion, integrating STEM-based coding effectively enhanced teachers’ CT skills and pedagogical competence while supporting the goals of Indonesia’s Merdeka Curriculum.